Implementasi Evidence Based Nursing Pada Pasien Rematik : Studi Kasus - Octa, Alvina Ramicci; Febrina, Wiwit (REAL in Nursing Journal, 2020)
Background: Rheumatoid is a disease that has long been known and is widespread throughout the world that symmetrically experiences inflammation so that swelling, pain and eventually cause damage to the inside of the joints and will disrupt the activities / work of patients. The main symptom of rheumatism is pain in the affected joint, especially when moving. Generally arise slowly. At first it feels stiff, then arises pain that decreases with rest. Family support plays an important role in nursing care provided. To achieve good treatment outcomes, implementation of evidence-based nursing is needed. Method: this case study aims to present the implementation of evidence-based nursing with complementary therapy, warm and progressive ginger compresses applied for 1 week.. Results: After each intervention given in combination the pre and post results show that before the intervention is given, the pain scale at the joint 5 after the intervention is given the pain scale 2. Conclusion: : Complementary therapy of warm ginger compresses performed 1 time in the day as long as 7 days for 20 minutes, showing pain results the patient's joints and bones are reduced